Flexible Asymmetric Supercapacitors Based on Nitrogen‐Doped Graphene Hydrogels with Embedded Nickel Hydroxide Nanoplates. Issue 10 (20th April 2016) - Xie, Hao; Tang, Shaochun; Li, Dongdong; Vongehr, Sascha; Meng, Xiangkang
Abstract: To push the energy density limit of supercapacitors (SCs), new electrode materials with hierarchical nano‐micron pore architectures are strongly desired. Graphene hydrogels that consist of 3 D porous frameworks have received particular attention but their capacitance is limited by electrical double layer capacitance. In this work, we report the rational design and fabrication of a composite hydrogel of N‐doped graphene (NG) that contains embedded Ni(OH)2 nanoplates that is cut conveniently into films to serve as positive electrodes for flexible asymmetric solid‐state SCs with NG hydrogel films as negative electrodes. The use of high‐power ultrasound leads to hierarchically porous micron‐scale sheets that consist of a highly interconnected 3 D NG network in which Ni(OH)2 nanoplates are well dispersed, which avoids the stacking of NG, Ni(OH)2, and their composites. The optimal SC device benefits from the compositional features and 3 D electrode architecture and has a high specific areal capacitance of 255 mF cm −2 at 1.0 mA cm −2 and a very stable, high output cell voltage of 1.45 V, which leads to an energy density of 80 μW h cm −2 even at a high power of 944 μW cm −2, considerably higher than that reported for similar devices. The devices exhibit a high rate capability and only 8 % capacitance loss over 10 000 charging cycles as well as excellent flexibility with no clear performance degradation under strong bending. Abstract : Bend me, shape me : We report the fabrication of a new composite hydrogel of N‐doped graphene (NG) that contains embedded Ni(OH)2 nanoplates. Asymmetric solid‐state supercapacitors prepared from such hydrogel films as positive electrodes deliver high energy densities. The high output cell voltage allows a light‐emitting diode to be operated with a single capacitor.